(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article explores innovative approaches to the development of packaging for food and processing industry products in the context of modern environmental, technological and economic challenges. The current trends in the development of packaging materials are analyzed, in particular the introduction of biopolymers, active and intelligent packaging systems that are able not only to ensure product safety, but also to interact with it, responding to changes in the internal environment. The advantages of using biodegradable materials based on polylactide, starch and cellulose are considered, as well as problems associated with their mechanical stability and production cost. Particular attention is paid to the concepts of “smart packaging” and “active packaging”, which involve the use of sensory elements, freshness indicators, RFID technologies and nanomaterials. The paper provides a comparative characteristic of traditional and modern packaging materials, and also presents a scheme for introducing innovative solutions into packaging production, which takes into account the stages from material selection to environmental efficiency assessment. The importance of combining the functionality of packaging with the principles of sustainable development and circular economy is emphasized. The results obtained allow us to formulate recommendations for further improvement of packaging technologies for the food industry, aimed at reducing the negative impact on the environment, improving product quality and efficiency of logistics processes. The article has practical value for specialists, scientists and manufacturers working on the implementation of environmentally friendly innovations in the packaging industry.